2023
DOI: 10.3389/fcimb.2023.1093967
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of oral microbe on intestinal microbiota and the illness

Abstract: Over the past decade, the association between oral health, intestinal microbiota, and systemic diseases has been further validated. Some oral microbial species have been isolated from pathological intestine mucosa or feces and identified as biomarkers for intestinal diseases. A small proportion of oral microbiome passes through or colonizes the lower gastrointestinal tract, even in healthy individuals. Opportunistic pathogens from the oral cavity may expand and participate in the occurrence and progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…Gut involvement of tuberculosis infection likely plays a more important role because tuberculosis-induced aplastic cytopenia has been reported merely in disseminated tuberculosis instead of isolated pulmonary tuberculosis. Gastrointestinal tuberculosis induces not only inflammatory lesions of its own but also gut dysbiosis, resulting in increased epithelial permeability and compromised barrier function in infected and downstream intestinal segments[ 28 , 29 ]. The gastrointestinal tract is an organ that hosts the most abundant lymphatic tissues and microbial community and therefore can provide sufficient activated immune cells and continuously supply exogenous antigens from both pathogenic and commensal microbes to initiate and perpetuate deranged autoimmunity in the context of increased epithelial permeability and gut inflammatory conditions[ 30 - 33 ], leading to autoimmune hematopoietic failure[ 34 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut involvement of tuberculosis infection likely plays a more important role because tuberculosis-induced aplastic cytopenia has been reported merely in disseminated tuberculosis instead of isolated pulmonary tuberculosis. Gastrointestinal tuberculosis induces not only inflammatory lesions of its own but also gut dysbiosis, resulting in increased epithelial permeability and compromised barrier function in infected and downstream intestinal segments[ 28 , 29 ]. The gastrointestinal tract is an organ that hosts the most abundant lymphatic tissues and microbial community and therefore can provide sufficient activated immune cells and continuously supply exogenous antigens from both pathogenic and commensal microbes to initiate and perpetuate deranged autoimmunity in the context of increased epithelial permeability and gut inflammatory conditions[ 30 - 33 ], leading to autoimmune hematopoietic failure[ 34 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also noticed a peculiar increase in the relative abundance of bacterial species characteristic of the oral microbiota in CDD, including Granulicatella adiacens, Streptococcus salivarius and Veillonella parvula. Oral-derived microorganisms have been shown to trigger inflammatory responses, promoting their translocation within the intestinal microenvironment 35 , creating a potentially harmful vicious cycle 36 . Intestinal inflammation, as evidenced by recent studies 37 , has been shown to not only promote the occurrence of seizures but also to influence the responsiveness to anti-seizure medication (ASMs) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We also noticed a peculiar increase in the relative abundance of bacterial species characteristic of the oral microbiota in CDD, including Granulicatella adiacens, Streptococcus salivarius and Veillonella parvula. Oral-derived microorganisms have been shown to trigger in ammatory responses, promoting their translocation within the intestinal microenvironment 35 , creating a potentially harmful vicious cycle 36 . Intestinal in ammation, as evidenced by recent studies 37 , has been shown to not only promote the occurrence of seizures but also to in uence the responsiveness to anti-seizure medication (ASMs) 38 .…”
Section: Discussionmentioning
confidence: 99%